One-hand guidewire introducer kit for ultrasound-guided central venous catheterization: a proof-of-concept study - Seung Jin Eo; Dae Sung Ryu; Chae Eun Yun; Yubeen Park; Dong-Sung Won; Ji Won Kim; Song Hee Kim; Jung-Hoon Park; Doo-Hwan Kim (Scientific Reports)
Abstract Despite ultrasound guidance for central venous catheterization (CVC), the first-attempt success rate has remained around 52.6−62.1%. A significant reason is that the needle can sometimes be dislodged from the punctured vein during hand shifts. Here, a novel one-hand guidewire introducer (OGI) kit was developed to perform guidewire insertion in the central vein, eliminating hand shifts. To establish a protocol, the OGI kit was validated using a central line training phantom. A total of 48 randomized trials of guidewire insertion in the internal jugular vein in eight pigs were performed using either the conventional kit (group A) or the OGI kit (group B). All trials were technically successful with all eight pigs. First-attempt success rate (50% vs. 75%, p = 0.035) and global rating scale (12 (5−15) vs. 14 (8−15), p = 0.011) were significantly lower in group A than in group B. The number of needle redirections and guidewire insertions, time to guidewire insertion, and procedure-related complications were significantly higher in group A than in group B. Guidewire insertion using a novel OGI kit could be a promising approach for real-time ultrasound-guided CVC as it offers greater clinical usefulness.